Attending to the non-preferred hand improves bimanual coordination in children - Pellegrini, A. M.; Andrade, E. C.; Teixeira, L. A. (Elsevier B.V., 2004)
The effect of attentional focus in bimanual coordination was investigated from a developmental perspective by examining performance of right- and left-handed children, 5-8-years and 9-12-years old, on bimanual reciprocal tapping tasks. Attentional focus was either specified, by asking the children to attend to the preferred or to the non-preferred hand, or unspecified for the execution of the tasks. When attention was oriented to the non-preferred hand we found a reduced movement time and a lower frequency of errors. Performance differences for handedness and age-groups were observed when the children were oriented to attend to the preferred hand or when there was no instruction regarding attention. These differences in performance were eliminated when attention was oriented to the non-preferred hand. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: bimanual coordination; attention; handedness; motor development